Analisis Strategi Pemasaran UD. Arif Bersaudara Menggunakan Pendekatan SWOT dan QSPM: - Suparno; Khoirotul Ilmiyah; Eva Nur Mazidah (HATTA : Jurnal Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
Competition in the songkok (traditional cap) industry in Gresik Regency has become increasingly intense, especially for small enterprises such as UD. Arif Bersaudara, which face challenges in maintaining competitiveness amid changing market trends and consumer preferences. This study aims to analyze effective marketing strategies for UD. Arif Bersaudara by identifying internal and external factors and determining the most appropriate strategic priorities for business development. The research employs the SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis to identify strategic factors and the QSPM (Quantitative Strategic Planning Matrix) to determine the order of strategic priorities. Data were collected through questionnaires distributed to 92 respondents and analyzed quantitatively using weighting and attractiveness score calculations. The results show that the total IFE Matrix score is 4.80 and the EFE Matrix score is 4.772, placing UD. Arif Bersaudara in the “Grow and Build” strategic position. Based on the QSPM results, the main priority strategy is to leverage superior product quality, design variations, and size diversity to capture opportunities in digital and international markets, with the highest TAS value of 8.37. The study concludes that UD. Arif Bersaudara should focus its strategy on improving product quality and implementing digital marketing to strengthen competitiveness. The strength of this research lies in the application of the combined SWOT–QSPM methods, which provide measurable analytical results, while its limitation lies in the relatively small and region-specific number of respondents. Future research is recommended to expand respondent coverage and incorporate digital marketing–based analysis to make MSME marketing strategies more adaptive to technological developments.